CPAP acceptance and adherence in OSA patients in lower northern region part of Thailand - Prakassajjatham, Mantana; Chantim, Chanida (Chulalongkorn Medical Journal, 2023)
Background: Continuous positive airway pressure (CPAP) is the mainstay in obstructive sleep apnea (OSA) treatment. Good CPAP adherence reduces many risks of diseases and improves the overall quality of life. Objective: The purpose of this study was to determine the acceptance and adherence to CPAP therapy among Thai patients with OSA who attend an otorhinolaryngology sleep clinic. Methods: This retrospective study was conducted at the otorhinolaryngology sleep clinic, Naresuan University Hospital, Thailand between January 2015 and October 2021. The study enrolled all patients over 18 years old with OSA diagnosis. The patients were scheduled for follow-up appointments at least two weeks after their initial treatment and at the intervals determined by their condition. Results: There were 232 patients who matched the criteria for inclusion. The subjects of this study were predominantly obese elderly males. The mean Apnea-hypopnea index (AHI) was 40.8 ± 26.9 events/hour. The use of CPAP was accepted by 69.4% of the subjects. Short-term CPAP adherence was 77.2% in 123 patients, whereas long-term CPAP adherence was 72.5% in 102 patients. Male gender, lower body mass index (BMI), and a more favorable perception of the disease were all observed in the short-term adherence group. In the long-term adherence group, the high prevalence was found in patients using auto-positive airway pressure machines (APAP) and AHI was normalized after CPAP utilization. Conclusion: The acceptance rate, as well as short and long-term adherence, was around 70.0%. Acceptance of CPAP is related to advanced age, having a bed companion, financial coverage for CPAP machine, positional sleep apnea, higher disease severity, and disease awareness. Male gender, higher BMI, a more favorable perception of the disease, use of APAP and the normalization of AHI after CPAP treatment had a significantly higher prevalence in adherence group compared to non-adherence group.